Barriers to access maternal and child health services in humanitarian settings of Ethiopia: a systematic review and meta-analysis - Amare Simegn; Tigabu Munye Aytenew; Yohannes Tesfahun; Yitayal Ayalew Goshu; Diriba Teshome; Temesgen Lingerh Endalew; Sheganew Fetene; Atalel Fentahun Awedew; Demewoz Kefale (Conflict and Health, 2026)
Abstract Background The provision of maternity and child health (MCH) services is severely hampered by Ethiopia’s humanitarian problems, which are caused by natural catastrophes, displacement, and conflict. Improving health outcomes for disadvantaged communities requires an understanding of the barriers to receiving these services. Methods We followed the standards of PRISMA 2020 guideline when conducting our systematic review and meta-analysis. The databases PubMed, Scopus, Embase, and CINAHL were searched. Grey literature and Google Scholar were used to find articles published from 2015 to 2025. Tools from the Joanna Briggs Institute were used to evaluate quality. A socio-ecological model (SEM) was used to synthesize the narrative. Results Twenty-four studies were deemed eligible for inclusion. According to the evaluation, a number of complex obstacles significantly impeded the availability and use of maternity and child health (MCH) services in Ethiopia’s conflict-affected areas. Individual barriers were low maternal education, fear of insecurity, and a lack of knowledge about accessible options. Household decision-making processes, a lack of spouse support, and gender-based limitations that impede women’s autonomy were examples of interpersonal hurdles. Long distances, disruptions in transit, the destruction of infrastructure, and prevalent cultural or religious views were all considered community-level concerns. Conclusion Access to MCH services is restricted in Ethiopia’s humanitarian contexts by a number of interconnected barriers. Strengthening mobile health teams, restoring functional referral systems, expanding maternity waiting homes, and supporting community health workers may improve access to essential maternal and child health services in humanitarian settings in Ethiopia.